Participation in non-formal adult education within the European context: examining multilayer approach - Vaculíková, Jitka; Kalenda, Jan; Kočvarová, Ilona (Frontiers in Education, 2024)
Participation in non-formal adult education (NFE) is considered an essential part of lifelong learning, aiming to foster the development of individuals and societies. This significance is particularly evident today, given the era of extensive digitalization and disruptive technological advances. Nevertheless, not all adults participate in organized learning and have equal chances. Therefore, this study addresses the absence of up-to-date comparative findings on participation in NFE in the post-COVID-19 world. To this end, we examine current trends in NFE participation in four European countries: Sweden, Germany, the United Kingdom, and the Czech Republic (RQ1), where we explore the impact of key micro (social and behavioral), meso (job-related), and macrolevel (country-specific) factors on this participation (RQ2). Our findings indicate that NFE participation remained relatively stable in 2022 compared to 2016, except for Sweden and Germany, which achieved higher participation rates. However, differences in participation between countries are diminishing. Simultaneously, NFE participation is becoming increasingly joboriented and receives more support from employers. However, it is important to note that inequality in access to NFE persists, as the main predictors of NFE participation, such as learning intentions, educational attainment, economic and occupational status, remain consistent, regardless of the participants' economic activity and country of birth. This underscores the enduring significance of a key concept behind this study: the willingness to engage in organized NFE exhibits a complex structure with multiple layers.